PRESERVING BIODIVERSITY: THE ROLE OF JUDICIARY IN UPHOLDING INTERNATIONAL CONVENTIONS WITHIN ECOSYSTEM PROTECTION - Singh, Vineet Pratap (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Biodiversity is essential for the health and functioning of ecosystems, providing critical ecosystem services and supporting human well-being. However, biodiversity erosion poses significant threats to ecosystems and the planet’s sustainability. International environment agreements, like the Convention at Ramsar on wetlands and on Biological Diversity (CBD), are central to advancing global efforts to conserve the biodiversity. These treaties outline key principles and obligations that encourage countries to adopt sustainable development practices, safeguard ecosystems, and manage natural resources responsibly. By fostering international collaboration and setting shared conservation targets, these conventions significantly contribute to maintaining ecological balance and promoting long-term sustainability. This research article examines the role of judiciaries in upholding international conventions within ecosystem protection. This article undertakes a thorough examination of judicial interpretations, statutory frameworks, and scholarly analyses to investigate the role of judiciaries in implementing international conventions aimed at mitigating biodiversity loss and ecosystem degradation. Through a detailed review of relevant case law and academic literature, the study highlights how courts contribute to the enforcement of international environmental obligations, thereby strengthening the legal mechanisms designed to protect ecological systems and promote sustainable environmental governance. The article also analyzes the challenges and opportunities for judiciaries in promoting ecosystem protection, including issues of jurisdiction, legal standing, and enforcement mechanisms. By highlighting the importance of judicial intervention in biodiversity conservation, this article aims to contribute to ongoing efforts to safeguard ecosystems and promote sustainable development.